DIFFERENTIAL MICRO-MODELLING AND DYNAMIC ASSESSMENT: A FRAMEWORK FOR DEVELOPING PRE-SERVICE ENGLISH TEACHERS’ METHODOLOGICAL COMPETENCE - Maxliyoxon Yuldasheva Ahmadjon qizi (International Journal of Literature and Language Studies, 2026)
This study addresses a critical gap in foreign language teacher education: the cognitive overload and evaluation subjectivity experienced by pre-service teachers during traditional macro-teaching experiences. Operating within a competency-based paradigm, this paper presents a structured pedagogical framework combining Differential Microteaching with Dynamic Assessment Rubrics. Conducted with English philology students, the empirical research isolates core pedagogical sub-skills—specifically Classroom Management, Instructional Clarity, Teacher Talking Time (TTT) optimization, and Delayed Error Correction—and subjects them to target-driven, micro-scale practice. Methodological progress was measured using an objective quantitative and qualitative diagnostic matrix. The empirical results demonstrate that decoupling the complexities of complete lesson delivery into isolated, dynamically assessed micro-components significantly accelerates the acquisition of pedagogical fluency, minimizes instructional anxiety, and fosters high-level analytical self-awareness in novice language educators.